Perceived offensiveness to the self, not that to others, is a robust positive predictor of support of censoring sexual, alcoholic, and violent media content - Zhang, Jinguang (Frontiers in Psychology, 2023)
Harm and offense are two important notions in legal discussions on the extent to which one’s freedom may be limited. Prior research on the third-person effect found that perceived media harm on others, not perceived media harm on the self, is a robust positive predictor of support of censoring socially undesirable media content (e.g., pornography). In comparison, how offensiveness perceptions predict censorship support is not clear. Drawing on moral foundations theory, we test here how perceived media offensiveness to the self compared with 1) perceived media offensiveness to others and 2) perceived media harm on others would predict censorship support. We conducted two cross-sectional survey studies in the U.S. to address this question with sexual, alcoholic, and violent media content as test cases. In Study 1 (N = 544 undergraduates), we measured perceived media offensiveness to the self, that to others, and censorship support. In Study 2 (N = 727 non-student adults), we also measured perceived media harm on the self and others. As in prior research, we found that people perceive sexual, alcoholic, and violent media content to harm other viewers more strongly than it harms themselves, and the perception of how much others are harmed tracks perceivers’ censorship support. In contrast, while people also perceive the three types of media content to offend other viewers more strongly than they offend the self, the perception of how much others are offended tracks censorship support to a significantly lesser extend or does not track at all. Instead, the perception of how much the self is offended does. These findings add to the work on moral foundations theory that distinguish between how the care/harm and sanctity/degradation foundations relate to moral judgments. These findings also suggest that the current theorizing of the third-person effect needs to expand to reconcile the seemingly inconsistent results on harm- and offensiveness perceptions differently relate to censorship support. The care/harm and sanctity/degradation foundations may underly how harm- and offensiveness perceptions predict censorship support. However, several “anomalous” findings need to be accounted for before moral foundations provide a comprehensive explanation of the third-person effect. .